Optimization of distributed generation placement in distribution network based on queen honey bee migration algorithm - Alif Dhurrotul Fachriyyah; Aripriharta Aripriharta; Sujito Sujito; Muchamad Wahyu Prasetyo; Muhammad Cahyo Bagaskoro; Norzanah binti Rosmin; Saodah Omar; Gwo Jiun Horng (Journal of Mechatronics, Electrical Power, and Vehicular Technology, 2025)
In this research, an optimal distributed generation (DG) placement method for radial distribution systems based on queen honey bee migration (QHBM) and backward forward sweep (BFS) is presented. The suggested approach makes it possible to evaluate DG placement options in terms of branch currents, voltage profiles, and active power losses in a physically consistent manner. DG units are characterized as photovoltaic-based sources operating at unity power factor using an explicit net load formulation at the bus level, ensuring a clear interplay between DG injection and current-based load flows. Throughout the optimization process, a constraint-aware migration technique is employed to explicitly impose voltage limitations with the goal of minimizing overall active power losses while maintaining bus voltage magnitudes within allowable bounds. The proposed method was tested on an IEEE 69-bus radial distribution system to evaluate its performance. The results show that the placement of three DG units with a total installed capacity of approximately 2600 kW at buses 61, 64, and 17 produces a significant improvement in network operation. Under this arrangement, active power losses drop markedly from 224.4419 kW in the base condition to 72.7840 kW, corresponding to a reduction of 67.6 %. At the same time, the lowest bus voltage rises from 0.9104 p.u. to 0.9931 p.u., while voltage levels across the network consistently remain within the allowable range of 0.95–1.05 p.u. The study's findings suggest that QHBM-BFS can be used as a trustworthy and useful method for figuring out where DG should be placed in radial distribution systems.